Influence of an Additive on Zinc Electrodeposition in the Ionic Liquid 1‐Ethyl‐3‐methylimidazolium Trifluoromethylsulfonate. Issue 8 (5th May 2015) - Liu, Zhen; Zein El Abedin, Sherif; Borisenko, Natalia; Endres, Frank
Abstract The influence of an additive, 1, 2‐dimethyl‐3‐(trifluoromethyl)‐1H‐pyrazol‐2‐ium trifluoromethylsulfonate, on the electrodeposition of zinc from 0.2 M Zn(TfO)2 in the ionic liquid 1‐ethyl‐3‐methylimidazolium trifluoromethylsulfonate ([EMIm]TfO) at room temperature was investigated by using cyclic voltammetry, scanning electron microscopy, and X‐ray diffraction. Both in the presence and absence of the additive, the bulk electrodeposition of Zn is obtained at −0.7 V versus Zn. In the presence of the additive, two more reduction peaks, which correlate with the reduction of the additive, are observed at electrode potentials more negative than the bulk deposition of Zn. Both the concentration of the additive and the cathodic reverse potentials influence the zinc stripping process. Furthermore, it was found that the adsorption of the additive on the electrode surface obviously inhibits Zn nucleation and, thus, influences the morphology of the deposit as well as the preferred orientation.